Web Based E-Commerce System Design at EXO Shop Using The Waterfall Method - Aulia Jannah; Adila Mawadda Meuraxa; Azzahrah Azzahrah (Ilmu Bersama Center, 2023)
Online shop websites can facilitate company or shop promotions and make it easier for consumers to get information about products from sellers or shops. Limited product merchandising prevented stores from increasing sales, and poor inventory control and manual reporting negatively impacted stores, making sales and inventory reporting difficult. The purpose of this research is to use the waterfall method to create an e-commerce website that can be opened online with an internet network. The method used by researchers in this study is the waterfall method. This method is used by researchers to develop software systems through a sequential software life cycle, starting with analysis, design, coding, and testing. System themes use PHP, HTML, CSS and Notepad while the database uses My-Sql which is accessed via XAMPP localhost. This research produces a web-based e-commerce application that provides real-time stock information, sales reports, stock reports and stores can advertise the products being sold. So that the process of reporting and controlling inventory data is carried out properly, and store marketing has a wider reach, so that store sales can increase.